Clinical and Molecular Characterization of Patients with Fructose 1,6-Bisphosphatase Deficiency - Li, Niu (Int J Mol Sci, 2017)
Fructose-1,6-bisphosphatase (FBPase) deficiency is a rare, autosomal recessive inherited disease caused by the mutation of the FBP1 gene, the incidence is estimated to be between 1/350,000 and 1/900,000. The symptoms of affected individuals are non-specific and are easily confused with other metabolic disorders. The present study describes the clinical features of four Chinese pediatric patients who presented with hypoglycemia, hyperlactacidemia, metabolic acidosis, and hyperuricemia. Targeted-next generation sequencing using the Agilent SureSelect XT Inherited Disease Panel was used to screen for causal variants in the genome, and the clinically-relevant variants were subsequently verified using Sanger sequencing. Here, DNA sequencing identified six variations of the FBP1 gene (NM_000507.3) in the four patients. In Case 1, we found a compound heterozygous mutations of c.704delC (p.Pro235GlnfsX42) (novel) and c.960_961insG (p.Ser321Valfs) (known pathogenic). In Case 2, we found a compound heterozygous mutations of c.825 + 1G>A and c.960_961insG (both were known pathogenically). In Case 3, a homozygous missense mutation of c.355G>A (p.Asp119Asn) (reported in ClinVar database without functional study) was found. Case 4 had a compound heterozygous mutations c.720_729del (p.Tyr241GlyfsX33) (novel) and c.490G>A (p.Gly164Ser) (known pathogenically). Further in vitro studies in the COS-7cell line demonstrated that the mutation of ASP119ASN had no impact on protein expression, but decreased the enzyme activity, and with which the clinical significance of Asp119Asn can be determined to be likely pathogenic. This report not only expands upon the known spectrum of variation of the FBP1 gene, but also deepens our understanding of the clinical features of FBPase deficiency.